Airborne and indigenous microbiomes co‐drive the rebound of antibiotic resistome during compost storage. (26th July 2021) - Liao, Hanpeng; Bai, Yudan; Liu, Chen; Wen, Chang; Yang, Qiue; Chen, Zhi; Banerjee, Samiran; Zhou, Shungui; Friman, Ville‐Petri
Summary: Composting is widely used to reduce the abundance of antibiotic resistance genes (ARGs) in solid waste. While ARG dynamics have been extensively investigated during composting, the fate and abundance of residual ARGs during the storage remain unexplored. Here, we tested experimentally how ARG and mobile genetic element (MGE) abundances change during compost storage using metagenomics, quantitative PCR and direct culturing. We found that 43.8% of ARGs and 39.9% of MGEs quickly recovered already during the first week of storage. This rebound effect was mainly driven by the regrowth of indigenous, antibiotic‐resistant bacteria that survived the composting. Bacterial transmission from the surrounding air had a much smaller effect, being most evident as MGE rebound during the later stages of storage. While hyperthermophilic composting was more efficient at reducing the relative abundance of ARGs and MGEs, relatively greater ARG rebound was observed during the storage of hyperthermophilic compost, exceeding the initial levels of untreated sewage sludge. Our study reveals that residual ARGs and MGEs left in the treated compost can quickly rebound during the storage via airborne introduction and regrowth of surviving bacteria, highlighting the need to develop better storage strategies to prevent the rebound of ARGs and MGEs after composting.